Biometric hoof evaluation of athletic horses of show jumping, barrel, long rope and polo modalities - Sampaio,Breno Fernandes Barreto (2013)
This study aimed to evaluate, through biometry, the forelimb hoof of horses participating in show jumping, barrel, long rope and polo competitions. Thirty subjects were assessed in relation to each competition (total of 120 animals). The linear measurements (cm) included the dorsal length of the toe; medial and lateral lengths of the quarter; medial and lateral heights of the quarter; lateral and medial lengths of the heel; medial and lateral heights of the heel; hoof length; hoof width; frog length; and frog width. The following angles (°) were measured: toe angle, pastern angle, heel angle and shoulder palette. The length of the horseshoe, coronet circumference and body weight were also assessed. With the use of hoof biometric evaluation was possible to identify the imbalances of forelimb in athletic horses and the most common were broken-backward hoof angle, with 96.7% of the animals showing this in the right forelimb (RFL) and 95.8% in the left forelimb (LFL); and contracted heels, with 95.0% in the RFL and 87.6% in the LFL. The competition type in which greatest numbers of hoof balance abnormalities were shown was the long rope, followed by the barrel. There were high frequencies of medial/lateral imbalance in all the sports. We conclude that animals used in functional tests have a high incidence of hoof balance abnormalities in the forelimbs.